Beyond "two source theory" and "sola Scriptura": ecumenical perspectives on Scripture and tradition - Moss, R. (Acta theologica, 2015)
A major source of doctrinal dispute between Catholicism and Protestantism over the centuries has revolved around the relationship between Scripture and Tradition. Does Scripture as the source of Revelation stand alone as in sola scriptura or does Scripture need to be interpreted and understood within the tradition from which it emerged and by which it should be understood. The Constitution, Dei Verbum, promulgated by the Second Vatican Council and the two Protestant Conferences held almost contemporaneously at Oberlin and Montreal suggest a possible convergence beyond the impasse. Protestantism needs to acknowledge the importance of tradition in biblical interpretation while Catholicism having effectively abandoned the two source theory of revelation needs criteria to distinguish between authentic tradition closely linked to scripture and an inauthentic tradition.